The Impact of Comorbidities on the Effectiveness of Noninvasive Ventilation in Patients with Chronic Obstructive Pulmonary Disease - Mujaković, Aida; Mlačo-Vražalić, Nejra; Prohić, Nejra; Mlačo, Akif (Acta medica Lituanica, 2026)
Background: Noninvasive ventilation (NIV) is a cornerstone treatment for hypercapnic respiratory failure in patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate the impact of selected comorbidities on the effectiveness of NIV in these patients, and to compare clinical characteristics and outcomes between continuous positive airway pressure (CPAP) and bilevel positive airway pressure (BiPAP) modalities.Materials and methods: This prospective, randomized, single-center study included 80 patients with hypercapnic respiratory failure due to COPD, randomized 1:1 to CPAP or BiPAP. Demographic and clinical data, comorbidities, vital signs, and arterial blood gas parameters were recorded at admission and during NIV. The primary outcome was pCO₂ reduction at the end of treatment compared with baseline.Results: Arterial hypertension significantly enhanced pCO₂ reduction with CPAP, but not with BiPAP. Systolic and mean arterial pressure independently predicted the magnitude of pCO₂ reduction, regardless of NIV modality. Patients treated with BiPAP more frequently had decompensated cor pulmonale and severe pulmonary hypertension, while pneumonia was more common in the CPAP group. NIV modality itself was not an independent predictor of pCO₂ reduction.Conclusion: Systemic hemodynamic status and arterial hypertension influence NIV effectiveness in hypercapnic COPD. The cardiovascular status should be considered alongside respiratory parameters when selecting the NIV strategy.